Integer Programming and Combinatorial Optimization 14th International Conference, IPCO 2010, Lausanne, Switzerland, June 9-11, 2010. Proceedings - Eisenbrand, Friedrich.; Shepherd, F. Bruce. (Lecture Notes in Computer Science, 2010)
This book constitutes the proceedings of the 14th International Conference on Integer Programming and Combinatorial Optimization, IPCO 2010, held in Lausanne, Switzerland in June 2010. The 34 papers presented were carefully reviewed and selected from 135 submissions. The conference has become the main forum for recent results in integer programming and combinatorial optimization in the non-symposium years.